Ecologie de l'avifaune aquatique des zones humides de la région d'Oum El Bouaghi - SAHBI Yasmine Imane (My University, 2022)
This study was conducted at seven (07) water bodies of the complex of wetlands of Oum el Bouaghi (highlands of eastern Algeria) to assess the structure and composition of the community of waterfowl that frequents the place, includes: garaets, chott, sebkha during a period that extends between the month of January 2014 until December 2015, Lake Timerganine represents the only freshwater body in the region. Ornithological censuses show the ecological role that play these aquatic environments for the protection of aquatic avifauna 67 species of 17 families. The richest family in species is that of the Anatidae (15 species in the Lake Timerganine and 11 species in Garaet Taref). From the point of view of numbers, the pink flamingo (Phoenicopteridae) and the shelduck (Anatidae) are the most represented species in the eco-complex of the wetlands of the region of Oum El Bouaghi, the coot Fulica atra (Rallidae) is the most represented species in the Timerganine Lake. The highest value of specific richness is noted in the lake Timerganine with a total of 57 species. The spatial occupation of waterbirds shows different distribution patterns according to their family. The Anatidae occupy the totality of the two wetlands, the Ardeidae generally observed near the phragmites, the limicoles frequent only the banks because of their small size and certain species of Laridae fly over the wetlands. We point out the importance of this complex for some species threatened with extinction, such as the marbled teal Marmaronetta angustirostris, the white-headed duck Oxyura leucocephala and the Ferruginous duck Aythya nyroca, hence the need for a management plan for these wetlands. The study of the diurnal activity rhythm of the two species shows that sleeping is the most dominant activity for the pink flamingo while feeding is the main activity for the shelduck in Graet Taref. -------------- الملخص أجريت هذه الدراسة على مستوى سبعة مسطحات مائية من مياه مجمع المناطق الرطبة بأم البواقي (مرتفعات شرق الجزائر) لتقييم ماهية وتوزيع الطيور المائية التي تتردد على هذه الأماكن، شملت هذه الدراسات ما يلي :انه في فترة جانفي 2014 إلى ديسمبر 2015 ، تعتبر قرعة تيمرقانين هي المسطح المائي ذو مياه عذبة الوحيد في المنطقة. و بينت الاحصائيات الدور الإيكولوجي الذي تلعبه هذه البيئات المائية لحماية الطيور المائية منها 67 نوعا من 17 أسرة.والعائلة الغنية بالأنواع هي الأناتيدا وجدنا (15 نوعا في قرعة تيمرقانين و 11 نوعا في قرعة الطارف (ومن وجهة النظر الفعالة قد تبين ان بط اللحام الوردي وبط التادورن هما أكثر الأنواع وجودا في المجمع البيئي للمناطق الرطبة بأم البواقي ، والأكثر تمثيلاً في بحيرة تيمرقانين هي بط الاسود foulque macroule كأكبر عدد متواجد من عائلة الراليدا.  في بحيرة تيمرقانين ب 57 نوعا. وتحتل هذه الطيور المائية عدة مناطق مختلفة وفقا لأسرتها. وتشغل الأناتيدات جميع الأراضي الرطبة ، وهي الأرديدا التي تلاحظ بشكل عام بالقرب من النباتات المائية ، وتكثر الطيور الساحلية على الضفاف فقط بسبب صغر حجمها ، كما تشغل بعض أنواع اللاريدات فوق المناطق الرطبة. ونلاحظ أهمية هذا المجمع بالنسبة لبعض الأنواع المهددة بالانقراض كبط السارسال ماربري وبط المارشيم ذو الراس الابيض ، والنيروكا سكوب ، ومن هنا تأتي الحاجة إلى انشاء خطة لتسييرو حفظ هذه المناطق الرطبة. تبين دراسة سلوك النوعين أن النوم هو النشاط الأكثر هيمنة في اللحام الوردي في حين أن سلوك الغذاء هو النشاط الرئيسي لبط التادورن بيلون في قرعة الطارف. ------------------- Cette étude a été mené au niveau de sept (07) plans d’eau du complexe de zones humides d’Oum el Bouaghi (hauts-plateaux de l’est Algérie) afin d’évaluer la structure et la composition de la communauté d’oiseaux d’eau qui fréquente les lieux, comprend :des garaets ,chott, sebkha pendant une période qui s’étale entre le mois de janvier 2014 jusqu'au décembre 2015, le lac Timerganine représente l’unique plan d’eau douce de la région. Des recensements ornithologiques montrent le rôle écologique qui jouent ces milieux aquatiques pour la protection de l’avifaune aquatique 67 espèces de 17 familles. La famille la plus riche en espèces est celle des Anatidés (15 espèces dans le Lac Timerganine et 11 espèces au Garaet Taref). Du point du vue effectif, les flamant rose (Phoenicoptéridés) et le tadorne de belon (Anatidés )sont les espèces les plus représentées dans l'éco-complexe des zones humides de la région d'Oum El Bouaghi, la Foulque macroule Fulica atra (Rallidés) est l’espèce la plus représentée au lac Timerganine . La valeur de richesse spécifique la plus élevée est notée dans le lac Timerganine avec un total de 57 espèces. L’occupation spatiale des oiseaux d’eau montre des différents modes de distribution selon leur famille. Les anatidés occupent la totalité des deux zones humides, les Ardeidés généralement observés près des phragmites, les limicoles ne fréquentent que les berges à cause de leur petite taille et certaines espèces des Laridés survolent sur les sites humides. nous signalons l’importance de ce complexe pour certaines espèces menacés d’extinction cas de la sarcelle marbrée Marmaronetta angustirostris, l’Erismature a tête blanche Oxyura leucocephala et le fuligule nyroca Aythya nyroca d’où la nécessité d’un plan de gestion de ces zones humides.L’étude du rythme d’activité diurne des deux espèces montre que le sommeil est l’activité la plus dominante chez le flamant rose tandis que l'alimentation est l'activité principale chez la tadorne de belon dans Graet Taref.